A Novel Algorithm for Generating pseudo Random Number- - Gangyi Hu; Weili Kou; Sumeth Yuenyong; Jian Qu (Journal of Digital Information Management, 2020)
This paper proposes a pseudo random number generation algorithm based on cellular neural networks. It used the hyper-chaos characteristics of the cellular neural networks and sets the appropriate parameters to generate the pseudo random number. The experimental results show that, compared with other similar algorithms, this algorithm has the characteristics of simple operation, low complexity, large key space, and good randomness. It can meet the needs of secure communication and network information security, which has good application prospects.